Essence and features of the discourse of romantic culture of love: an attempt of rethinking - V. E. Turenko, (Ukrainian Cultural Studies, 2018)
The article analyzes the nature of the romantic culture of love. Romantic love is seen as a love culture, which includes a set of beliefs, ideals, principles that have developed in the Middle Ages, and the idea of which passes from generation to generation, from one century to another. It is emphasized that the romantic culture of love is not only a discourse of passion and ethos of eros. This cultural-historical type of love absorbs the connotations agape, filia and storge. Consequently, the discourse of those who love in the romantic invariant is not focused solely on passion, it is also caring, understanding, responsibility, attention, sacrifice, etc. – aspects inherent in love-filia, love-storge and love-agape. It is proved that a discourse of romantic culture of love is not realized through the prism of "rose-colored glasses", but in the context of understanding that the emergence of this feeling inevitably generates a sense of vulnerability in both participants of the love discourse. The presence of sorrow in one of the participants of the discourse of love is one of the most characteristic and vivid signs of the romantic culture of love. From the philosophical point of view, various aspects of love affliction are considered as markers of truth and authenticity of feelings, relationships between lovers. Tears, in romantic love - is not the weakness of an object and/or subject of love discourse, but it is their strength, depth and basis for the continuation of their history of feelings. It turns out that in contrast to the modern post-romantic culture of love, in the romantic tradition, the basis of love relations is the maximum recognition of the person. The one who we love is given to us as a fact of life, as the world itself. Love for which the only truly significant and determining any choice is the value of a particular, separate personality. The person we love, in essence, cannot be the subject of evaluation. One may be neither reasonable, nor good, but he/she is capable of transforming a valuable world, revealing its unity, its ability to harmony and doomed to disharmony. The love of human to human (the subject of Love) is the path where all the faces and all the boundaries, that distinguish people from one or another affiliation, disappear.
Keywords: romantic love culture, love culture, human life, human love, courtly culture of love, philosophy of love